Effects of early and late slaughter age on carcass characteristics and meat quality of quail - Noorul Hidayah Md Saleh (2015)
Different slaughtering ages practiced by the farmers in quail farming sector could have resulted in slow growth of the quail meat production. Due to this reason, a study on the effects of slaughter age on carcass characteristics and meat quality in Japanese quail was carried out. The objective of this study was to determine the influence of slaughter age on carcass characteristics and meat quality in quail. This experiment involved a total number of 60 male Japanese quail which were randomly divided into two different slaughtering ages (28 and 35 d old). The birds selected for the 28 d old of slaughtering age were grouped as treatment 1 (T1), while the remaining birds assigned for the 35 d old of slaughtering age were grouped as treatment 2 (T2). The growth performance and carcass characteristics examined are live weight, carcass yield, carcass dressing percentage and chemical composition of the breast meat between the two different slaughter ages. Pectoralis major muscles were taken for the chemical composition and meat quality determination. The mean of pre-slaughter weight of Japanese quail was higher in the T2 group (197.6 g) with no difference when compared to those slaughtered from the T1. There were differences (p<0.05) in carcass yield between T1 and T2 despite no differences were noted in the dressing percentage. No difference in carcass weight was recorded between the treatments. Similarly, muscle pH, color and water holding capacity remained unaffected by the age of slaughtering.
Project paper - (B.Agric.(An.Sc.) - Universiti Putra Malaysia, 2015.